Understanding the Complexities : An Exploration of Internal and External Factors Affecting Student Accounting Learning Difficulties - Sriwedari, Tuti; Nurhayani, Ulfa; Sibarani, Choms Gary Ganda Tua; Sitompul, Haryani Pratiwi; Nurwendari, Weny (Jurnal Paedagogy, 2025)
This study examines factors influencing accounting learning difficulties among 138 students of the Accounting Education Program at Universitas Negeri Medan, with a sample of 117, which was determined using Slovin’s formula and purposive sampling. This study employed descriptive and verificative methods, and data was analyzed through Structural Equation Modeling (SEM) with Maximum Likelihood Estimation (MLE). Key findings reveal that interest in learning, motivation, talent, independent learning, and campus environment significantly impact learning difficulties. Specifically, higher interest, motivation, and talent, combined with a supportive campus environment, reduce accounting learning difficulties. The study highlights the importance of fostering motivation, independent learning, and a resource-rich environment to enhance academic success and prepare students for accounting careers.